Bullying Experience in Elementary School Students - Ratna Kustanti, Erin; Rahmandani, Amalia; Asih Febriyanti, Dinni (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the study was to determine the experience of bullying in elementary school students. The approach in the study was phenomenology qualitative and the analysis technique was IPA (Interpretative Phenomenological Analysis). This study used a qualitative method with IPA (Interpretative Phenomenological Analysis) approach. This research was conducted on 60 elementary school students selected trought purposive sampling. Data collection was conducted through semi-structured group interviews (Focus Group Discussion). The findings of this study are forms of bullying that occur in elementary students, namely physical bullying, verbal bullying and social bullying. The things that cause fear in school are hostile, ridiculed, bullied. The things that saddened the victims are ridicule, exclusion, hostility, bullied. The things caused anger in victims are being ridiculed, harassed, ostracized, despised. The victims of bullying experienced get harsh words, ridiculed, threatened, pinched, bitten, pulled his hair, beaten, pushed to fall, invited to fight. The feelings emerged after accepting bad treatments were marah, menyesal, takut, sedih, jengkel, sakithati, sabar, merasatidakditerima. The actions conducted after being the victims of bullying were angry, sorry, afraid, sad, annoyed, hurt, patient, feeling unaccepted. For the bullies, the forms of bullying were mocking, kicking, pushing a friend to fall, hit, pinched, biting. The feelings after conducted bullying were happy, angry, sad, feel guilty, do not want to repeat it again, uncomfortable heart. For bystander, the feelings emerged after being witnesses of bullying were sad, feel sorry, happy. The actions performed after being witness of bullying were help a friend, intervene, report to the teacher, advise, hit a naughty friend, fight a naughty friend.